The impact of socioeconomic status on outcomes in hepatocellular carcinoma: Inferences from primary insurance. (22nd August 2019) - Sellers, Cortlandt M.; Uhlig, Johannes; Ludwig, Johannes M.; Taddei, Tamar; Stein, Stacey M.; Lim, Joseph K.; Kim, Hyun S.
Abstract: Background: To investigate the impact of insurance status on outcomes in patients with hepatocellular carcinoma (HCC). Methods: Patients diagnosed with HCC in the cancer registry from 2005 to 2016 were retrospectively stratified by insurance group. Overall survival was assessed via Kaplan‐Meier curves and Cox proportional hazard models including potential confounders in multivariable analyses. Results: Seven hundred and sixty‐nine patients met inclusion criteria (median age 63 years, 78.8% male, 65.9% Caucasian). 44.5% had private insurance (n = 342), 29.1% had Medicare (n = 224), and 26.4% had Medicaid (n = 203). At diagnosis, Medicaid patients had higher rates of Child‐Pugh B (32.0%) and C disease (23.6%) vs Medicare (28.6% and 9.8%) and private insurance (26.9% and 6.7%, P  < 0.0001) and higher MELD scores (median 11.0) vs Medicare (9.0) and private insurance (9.0, P  = 0.0266). Across insurance groups, patients had similar distribution of American Joint Committee on Cancer stage, tumor size, and multifocal tumor burden. Patients with private insurance had the highest survival (median OS 21.9 months) vs Medicare (17.7 months) and Medicaid (13.0 months, overall P  = 0.0061). On univariate analysis, Medicaid patients demonstrated decreased survival vs private insurance (HR 1.40, 95% CI: 1.146‐1.715, P  = 0.0011). After adjustment for liver disease factors, this survival difference lost statistical significance (Medicaid vs private insurance, HR 1.02, 95% CI: 0.819‐1.266, P  = 0.8596). Conclusion: Medicaid was associated with advanced liver disease at HCC diagnosis; however, insurance status is not an independent predictor of HCC survival. Abstract : Medicaid is associated with advanced liver cirrhosis at time of hepatocellular carcinoma diagnosis. Primary insurance is not an independent predictor of survival.